2007 IEEE Congress on Evolutionary Computation 2007
DOI: 10.1109/cec.2007.4424587
|View full text |Cite
|
Sign up to set email alerts
|

Parallel BMDA with probability model migration

Abstract: Summary. The chapter presents a new concept of parallel BivariateMarginal Distribution Algorithm (BMDA) using the stepping stone communication model with the unidirectional ring topology. The traditional migration of individuals is compared with a newly proposed technique of probability model migration. The idea of the new adaptive BMDA (aB-MDA) algorithms is to modify the classic learning of the probability model (applied in the sequential BMDA [24]). In the proposed strategy, the adaptive learning of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It was also shown that the migration of a probabilistic model is better than the migration of individuals especially when setting β adaptively. Schwarz et al (2007) and Jaros and Schwarz (2007) proposed the use of a parallel bivariate marginal distribution algorithm (BMDA). The island model was used in a directed ring topology.…”
Section: Exchanging Probabilistic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that the migration of a probabilistic model is better than the migration of individuals especially when setting β adaptively. Schwarz et al (2007) and Jaros and Schwarz (2007) proposed the use of a parallel bivariate marginal distribution algorithm (BMDA). The island model was used in a directed ring topology.…”
Section: Exchanging Probabilistic Modelsmentioning
confidence: 99%
“…The introduction of Parallel EDAs is a new research direction that has been pursued in the past few years (Hiroyaso et al 2003;Ahn et al 2004;de la Ossa et al 2004de la Ossa et al , 2006Madera et al 2006;Schwarz et al 2007;Jaros and Schwarz 2007). The general idea is to have different EDAs running in parallel and exchanging information among them.…”
Section: Introductionmentioning
confidence: 99%
“…This second approach opens a new challenge: how should the different probabilistic models be combined? In general, the combination of the resident model with the immigrant one can be formalized by the following rule [19]:…”
Section: Distributed Estimation Of Distribution Algorithms: Dedasmentioning
confidence: 99%
“…Migration of individuals is a classic approach and has proven to obtain successful results in these and other Evolutionary Algorithms [2,4,9,28]. In addition, migration of models was explicitly developed for the distributed Estimation of Distribution Algorithms [1,11,12,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…migration operation) among different sub-groups at a certain evolutionary generation to generate new population and evolve the next generation on the basis of this cycle until the algorithm termination condition is satisfied. A migration operation is proven to be effective for EDAs and is known to yield good results [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%